2020
DOI: 10.3233/jad-190869
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Decline Among Sexual and Gender Minorities: Results from a U.S. Population-Based Sample

Abstract: The risk of dementia and mild cognitive impairment between older adults in same-sex relationships and those in opposite-sex relationships have been found to be statistically not different. However, studies examining subjective cognitive decline (SCD) among sexual and gender minority populations (SGM) are lacking. The primary objective was to determine if SGM report greater subjective cognitive decline (SCD) compared to non-SGM populations in a US population-based sample of non-institutionalized adults aged 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
1
24
5
Order By: Relevance
“…Another study found higher rates of self‐reported cognitive difficulties among racial/ethnic minorities, gender minorities, and those who identified their sexual orientation as other 12 . Finally, a study using only the 2016 BRFSS found no difference in SCD by SOGI; however, only eight US states administered both the SOGI and SCD modules in 2016, which resulted in a smaller sample of SGM adults (n = 1094) compared to our study 22 …”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Another study found higher rates of self‐reported cognitive difficulties among racial/ethnic minorities, gender minorities, and those who identified their sexual orientation as other 12 . Finally, a study using only the 2016 BRFSS found no difference in SCD by SOGI; however, only eight US states administered both the SOGI and SCD modules in 2016, which resulted in a smaller sample of SGM adults (n = 1094) compared to our study 22 …”
Section: Discussioncontrasting
confidence: 72%
“…12 Finally, a study using only the 2016 BRFSS found no difference in SCD by SOGI; however, only eight US states administered both the SOGI and SCD modules in 2016, which resulted in a smaller sample of SGM adults (n = 1094) compared to our study. 22 Another study using data from the National Alzheimer's Coordinating Center found no difference in risk of objective cognitive impairment (MCI and dementia) for same-sex couples compared to opposite-sex couples. 13 The researchers noted several study limitations in terms of recruitment bias, non-probability sampling, and potential biases in reporting and ascertainment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many LGBT older adults experiencing dementia risk factors, the association between LGBT identity and cognitive decline remains unclear. One cross‐sectional study 11 found a lack of association between LGBT identification and SCD, and another 12 found a lack of association between LGBT identity and mild cognitive impairment and dementia. More studies are required to elucidate the impact of LGBT identity on cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…remains unclear. One cross-sectional study 11 found a lack of association between LGBT identification and SCD, and another 12 found a lack of association between LGBT identity and mild cognitive impairment and dementia. More studies are required to elucidate the impact of…”
mentioning
confidence: 99%
“…In the presence of functional limitations, the experience of SCD would be compounded by a lower socio-economic gradient [ 31 ]. Older age, males, and Blacks are associated with having more disrupted IADLs [ 34 ]. For instance, older men are 64% more likely to report SCD than their counterparts [ 35 ].…”
Section: Introductionmentioning
confidence: 99%